2020
DOI: 10.3803/enm.2020.847
|View full text |Cite
|
Sign up to set email alerts
|

Association between Secondhand Smoke Exposure and Metabolic Syndrome in 118,609 Korean Never Smokers Verified by Self-Reported Questionnaire and Urine Cotinine

Abstract: Background: No study has reported the association between secondhand smoke (SHS) exposure and metabolic syndrome (MetS) in self-reported never smokers verified by both self-reported questionnaire and urine cotinine.Methods: A total of 118,609 self-reported and cotinine-verified never smokers (38,385 male; age 34.8±7.1 years) who participated in the Kangbuk Samsung Health Study between 2011 and 2016 were included. Cotinine-verified never smokers were defined as individuals with urinary cotinine <50 ng/mL. SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
6
2
Order By: Relevance
“…Our finding of an association between SHS and a high OR for MetS in both the male and female participants is important. A previous study 8 of 118,609 Korean participants over 18 years of age who self-reported that they were never-smokers and were verified through urinary cotinine analysis investigated the associations among SHS exposure, sex and prevalence of MetS, and reported a notably higher prevalence of MetS in both males and females exposed to SHS compared to those without exposure. In another large longitudinal study 22 of 71,055 non-smokers without MetS at baseline, the subjects were classified into continuous, former, new and no exposure to environmental tobacco smoke (ETS) groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of an association between SHS and a high OR for MetS in both the male and female participants is important. A previous study 8 of 118,609 Korean participants over 18 years of age who self-reported that they were never-smokers and were verified through urinary cotinine analysis investigated the associations among SHS exposure, sex and prevalence of MetS, and reported a notably higher prevalence of MetS in both males and females exposed to SHS compared to those without exposure. In another large longitudinal study 22 of 71,055 non-smokers without MetS at baseline, the subjects were classified into continuous, former, new and no exposure to environmental tobacco smoke (ETS) groups.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to secondhand smoke (SHS) is defined as currently being exposed to passive smoking indoors in the workplace or at home 8 . Tobacco smoke comprises many components, of which 20 carcinogens, and in particular polycyclic aromatic hydrocarbons and the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, are considered to play major roles in the development of lung cancer 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis highlighted that active smokers, including both current and former smokers, demonstrated an increased incidence of MetS compared to individuals who never smoked, with a pooled relative risk (RR) and 95% confidence interval (95% CI) of 1.26 (1.10–1.44) [ 5 ]. Additionally, findings from a Korean cohort study revealed a higher prevalence of MetS among women exposed to secondhand smoke than individuals who never smoked (5.8% vs. 4.6%; odds ratio (OR) = 1.17; 95% CI = 1.06–1.29; p < 0.001) [ 6 ]. Therefore, in this study, individuals who had never smoked and those not exposed to secondhand smoke were categorized into the healthy group (1 point).…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have revealed significant associations between individual lifestyles and MetS. For example, both active smoking and secondhand smoke exposure were positively associated with MetS [ 5 , 6 ]. A meta-analysis demonstrated that an increase of 10 metabolic equivalent of task (MET) h/week in leisure-time physical activity correlated with an 8% reduction in MetS incidence [ 7 ].…”
Section: Introductionmentioning
confidence: 99%